Adding invasive species biosurveillance to the U.S. Geological Survey streamgage network. Issue 8 (13th August 2019) - Sepulveda, Adam J.; Schmidt, Christian; Amberg, Jon; Hutchins, Patrick; Stratton, Christian; Mebane, Chris; Laramie, Matthew B.; Pilliod, David S.
Abstract: The costs of invasive species in the United States alone are estimated to exceed US100 billion per year, so a critical tactic in minimizing the costs of invasive species is the development of effective, early‐detection systems. To this end, we evaluated the efficacy of adding environmental (e)DNA surveillance to the U.S. Geological Survey (USGS) streamgage network, which consists of >8200 streamgages nationwide systemically visited by USGS hydrologic technicians. Incorporating strategic eDNA sample collection during routine streamgage visits could provide early‐detection surveillance of aquatic invasive species with minimal additional cost. For this evaluation, USGS hydrologic technicians collected monthly eDNA water samples, May–September 2018, from streamgages downstream of reservoirs in the Columbia River Basin thought to be vulnerable to invasive dreissenid mussel ( Dreissenidae spp.) establishment. We tested water samples for dreissenid mussel DNA and also for kokanee ( Oncorhynchus nerka ) and yellow perch ( Perca flavescens ) DNA; the two fishes were used to assess if streamgages are adequately located to provide early‐detection eDNA surveillance of taxa known to be present in upstream reservoirs. No Columbia River Basin streamgage samples met our criteria for being scored as positive for dreissenid DNA. We did detect kokanee and yellow perch DNA at all streamgages downstream of reservoirs where these species are known to occur. Field collection, laboratory analyses, and personnel time required for collection of four eDNA samples at a streamgage site cost US500–US600 (net). Given these results, incorporating eDNA biosurveillance into routine streamgage visits might decrease costs associated with an invasion since early detection maximizes the potential for eradication, containment, and mitigation.